Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1136/bmj.c5869
|View full text |Cite
|
Sign up to set email alerts
|

Population based screening for chronic kidney disease: cost effectiveness study

Abstract: Objective To determine the cost effectiveness of one-off population based screening for chronic kidney disease based on estimated glomerular filtration rate.Design Cost utility analysis of screening with estimated glomerular filtration rate alone compared with no screening (with allowance for incidental finding of cases of chronic kidney disease). Analyses were stratified by age, diabetes, and the presence or absence of proteinuria. Scenario and sensitivity analyses, including probabilistic sensitivity analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
128
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(130 citation statements)
references
References 62 publications
1
128
0
1
Order By: Relevance
“…These values are almost double those reported by Manns et al [14], who showed that the probability of death in a CKD cohort in Alberta, Canada, was 4.81% for patients aged \66 years and 13.29% for those aged [65 years. It is particularly interesting to note that 81% of the Canadian cohort had CKD stage 1 or 2, 18% had stage 3, and 1% had stage 4 or 5, whereas in our cohort, 50% had stage 1 or 2, 22% had stage 3, and 28% had stage 4 or 5.…”
Section: Discussionmentioning
confidence: 47%
“…These values are almost double those reported by Manns et al [14], who showed that the probability of death in a CKD cohort in Alberta, Canada, was 4.81% for patients aged \66 years and 13.29% for those aged [65 years. It is particularly interesting to note that 81% of the Canadian cohort had CKD stage 1 or 2, 18% had stage 3, and 1% had stage 4 or 5, whereas in our cohort, 50% had stage 1 or 2, 22% had stage 3, and 28% had stage 4 or 5.…”
Section: Discussionmentioning
confidence: 47%
“…Because unselective screening for kidney disease is not cost-effective (3,4), stratification of people at risk for CKD or progression of CKD is urgently needed in analogy to the highly successful risk calculators in the area of cardiovascular medicine (5). In people with diabetes, for example, screening for established CKD with measurements of albuminuria and eGFR has been shown to be cost-effective, with estimated costs of $18,650 (2009) per quality-adjusted life-year gained (6). Because primary prevention strategies are likely to be most cost-effective (6), it is also desirable to predict incident CKD in people with diabetes before microalbuminuria develops and CKD progression in those with microalbuminuria.…”
Section: Introductionmentioning
confidence: 99%
“…In people with diabetes, for example, screening for established CKD with measurements of albuminuria and eGFR has been shown to be cost-effective, with estimated costs of $18,650 (2009) per quality-adjusted life-year gained (6). Because primary prevention strategies are likely to be most cost-effective (6), it is also desirable to predict incident CKD in people with diabetes before microalbuminuria develops and CKD progression in those with microalbuminuria.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates were adjusted for age, sex, aboriginal status (registered First Nations and recognized Inuit), baseline GFR, social assistance, low-income subsidy, DM cause of CKD, and comorbidities (hypertension, DM, cancer, cardiovascular disease, myocardial infarction, heart failure, COPD, dementia, HIV/AIDS, liver disease, paraplegia, peptic ulcer disease, peripheral vascular disease, rheumatic disease). Estimates for transplantation, graft failure, and mortality in RRT states were drawn from our previous work in a similar dataset (Table 3) (16).…”
Section: Effectivenessmentioning
confidence: 99%